What’s the Time? Deciphering “Meter” in Razak Abdul Aziz’s 5 Early Songs - Mohd Fairuz, Zamani; Nur Fardilla Nadia, Abu Bakar; Tan, Jin Yin (2023)
The concept of meter in music has existed probably as old as music itself. Scholars had a variety of ways of categorizing meters in music. Recent investigations on the element of meter in contemporary art music show that scholars were more Europe-American-centric and only 10 Pantun Settings and Maria Zaitun by Razak Abdul Aziz were previously discussed academically, hence justifying the need to conduct this investigation. 5 Early Songs by Razak Abdul Aziz were written in 1980 (3 songs) and 1988 (2 songs). The researchers had chosen to conduct a systematic theoretical analysis of the chosen work using music theories proposed by Kostka et al. (2013), Kostka and Santa (2018), and Locke (2010). The analysis found that the use of the metric element is more complex in the two songs that were composed in 1988, suggesting that the 8-year gap the composer had given him time to acquire more musical materials, maturing over the years. It is hoped that this investigation would spark some interest among other scholars to conduct studies on the similar or other work(s) of Razak Abdul Aziz and possibly expand this to other Malaysian contemporary composers.